2017
DOI: 10.1093/infdis/jix263
|View full text |Cite
|
Sign up to set email alerts
|

Valganciclovir for the Suppression of Epstein-Barr Virus Replication

Abstract: Valganciclovir for the Suppression of Epstein-Barr Virus Replication Jessica Eve YagerChair of the Supervisory Committee:Professor Anna Wald Department of EpidemiologyEpstein-Barr virus (EBV), a common herpesvirus, is the main causative agent of infectious mononucleosis.Following primary infection, EBV persists in host cells and can cause B cell transformation, leading to the development of EBV-associated malignancies. The role for antiviral therapy in treating and preventing EBV-associated disease remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…One possible caveat when determining EBV DNA load is the use of valgangciclovir for preventing reactivation or primary infection of CMV. All patients received 3 months of valgangciclovir treatment initially after LTx; there are a few studies showing that valgangciclovir treatment reduces EBV load, which may have affected the results in this study [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…One possible caveat when determining EBV DNA load is the use of valgangciclovir for preventing reactivation or primary infection of CMV. All patients received 3 months of valgangciclovir treatment initially after LTx; there are a few studies showing that valgangciclovir treatment reduces EBV load, which may have affected the results in this study [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Yager et al [20] found that oral valganciclovir could inhibit EBV replication. In our patient, long-term oral ganciclovir therapy could inhibit EBV replication in the gastrointestinal tract; corticosteroids offered symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…The only promising treatment for resolving the EBV-infected neoplastic cells in CAEBV has been HSCT [19]. Although recent studies suggest some degree of effectiveness of valganciclovir for replication of EBV [2022], there have been no studies which found the effectiveness of valganciclovir or ganciclovir for CAEBV. In the present 2 cases, EBV-infected cells could not be eradicated, but the disease activities: inflammatory symptoms including uveitis were resolved after HSCT.…”
Section: Discussionmentioning
confidence: 99%